The Power of Contextual Learning: Dutch Colonialism in Ende-Lio and Its Effects on Students' Historical Awareness - Mbura, Ewilensia Magdalen; Yulifar, Leli; Suwirta, Andi (Universitas Pendidikan Mandalika, 2025)
This study aims to examine the effectiveness of local history-based teaching materials, specifically focusing on Dutch colonialism in Ende-Lio, in enhancing students' historical awareness at SMA Negeri 1 Wolowaru. The rationale behind this study is to make history learning more contextual, meaningful, and closely related to students' daily lives. By integrating local historical narratives into the classroom, students are expected to acquire factual knowledge and develop pride, responsibility, and a stronger attachment to their cultural heritage. This study employed a quasi-experimental method with a randomized pretest-posttest control group design. The population consisted of all eleventh-grade students at SMA Negeri 1 Wolowaru, with two classes selected as samples: XI-1 as the experimental group and XI-2 as the control group. Locally developed history modules on Dutch colonialism in Ende-Lio and a historical awareness questionnaire were used as instruments. Data analysis using descriptive statistical techniques revealed that students exposed to local history-based teaching materials achieved higher levels of historical awareness compared to those who experienced conventional learning methods. This finding confirms that embedding local historical contexts into history education provides a more engaging and meaningful learning experience, contributing to students' emotional engagement with the past and strengthening their awareness of national identity through local heritage.